PENGARUH STRATEGI BERSAING DENGAN MENGGUNAKAN KUALITAS DAN KERELASIAN PELANGGAN TERHADAP LOYALITAS PELANGGAN PADA INDUSTRI PERBANKAN - AULIA DANIBRATA (Jurnal Bisnis dan Akuntansi, 2013)
The aim of the research was to gain a thorough knowledge of the variables influencing customer loyalty at state owned banks. The variables were quality and customer relationships. Based on this research, it will be known what are the dimensions that give the dominant contribution of each variable, and the variables that effect. Research methods used for this research was verificative analysis consisted of hypothesis test by using statistical tests for causalities things. The analytical tools that being used is verificative as hypothesis measurement by using statistic test analysis tools name structural equation model. The analytical units consist of the customers of the bank. The number of samples is 135 with random sampling techniques for the respondents. The research shown that quality and customer relationships have significant influence on customer loyalty. It shown that in order to achieve high customer loyalty, the banks need to increase quality and customer relationships.